2014
DOI: 10.1021/ef5015742
|View full text |Cite
|
Sign up to set email alerts
|

Pyrolysis-Bridged Hybrid Power Systems and Their Application for Thermal Power Plants

Abstract: A hybrid power system based on coal pyrolysis and steam integration is proposed to improve the performance of power plants. The most outstanding features of the system are a pyrolysis process integrated with a circulating fluidized bed boiler and power generation by the steam integration. The model of the hybrid power system is set up by THERMOFLEX software and Aspen Plus. Results show that the thermal efficiency of pyrolysis process can achieve values of 90%–95%, and the majority of the energy used by the pyr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Fast pyrolysis is one efficient method for the thermochemical conversion of low-rank coals. Recent studies have shown that fast coal pyrolysis followed by gasification and combustion of the generated char is a more effective and environmentally friendly method for low-rank coal utilization compared with those of direct combustion. …”
Section: Introductionmentioning
confidence: 99%
“…Fast pyrolysis is one efficient method for the thermochemical conversion of low-rank coals. Recent studies have shown that fast coal pyrolysis followed by gasification and combustion of the generated char is a more effective and environmentally friendly method for low-rank coal utilization compared with those of direct combustion. …”
Section: Introductionmentioning
confidence: 99%
“…Poly-generation technologies combining low-and-mid temperature pyrolysis with combustion or gasication have been developed to implement the pre-extraction of volatiles from coal. [4][5][6][7] In most of these processes, coal is rst fed to a pyrolyzer to extract volatiles, and then the resulting char is sent to a combustor or gasier for heat/power or syngas production. Between the two reactors, hot ash from the combustor or gasier supplies heat for coal pyrolysis.…”
Section: Introductionmentioning
confidence: 99%